Selective laser sintering of polymer powder embedded with water-soluble flow additives

CN116056871BActive Publication Date: 2026-10-27EVONIK OPERATIONS GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180055017.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-08
Filing Date
2021-08-25
Publication Date
2026-10-27
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

虽然SLS 3D打印可用于各种各样的应用,但是一种制造条件不会对于所有材料都是合适的

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004111769180000241
    Figure BDA0004111769180000241
  • Figure BDA0004111769180000251
    Figure BDA0004111769180000251
  • Figure BDA0004111769180000261
    Figure BDA0004111769180000261
Patent Text Reader

Abstract

The present invention relates to a polymer powder, preferably a medical grade polymer powder, for use in selective laser sintering (SLS) including but not limited to medical, food and pharmaceutical applications. Preferably, the medical grade polymer is biodegradable and can be used to manufacture articles such as medical implants and tissue scaffolds. The powder is biocompatible and biodegradable and can include a flow additive. The flow additive can consist of a bone guided flow aid suitable for medical applications, a water soluble salt flow aid that dissolves during device degradation, or a combination of both. The water soluble salt flow aid is used for applications where no residual trace of the implant is observed in the tissue after device degradation.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Invention Technology

[0002] This invention relates to polymer powders, preferably medical-grade polymer powders, for use in selective laser sintering (SLS) for applications including but not limited to medical, food, and pharmaceutical fields. Preferably, the medical-grade polymer is biodegradable and can be used to manufacture articles such as medical implants and tissue scaffolds. The powder is biocompatible and biodegradable and may include flow additives. The flow additives may consist of bone-guided flow aids suitable for medical applications, water-soluble salt flow aids that dissolve during device degradation, or a combination of both. The water-soluble salt flow aids are used in applications where no implantation residue is observed in the tissue after device degradation. Background of the Invention

[0004] Selective laser sintering (SLS) has been widely used for metals and polymers. More specifically, polymer SLS primarily utilizes engineering polymers such as nylon, polyaryletherketone (PAE), polyetheretherketone (PEEK), polystyrene, and thermoplastic elastomers. These polymer grades are often not intended for medical applications; furthermore, currently commercially available engineering polymers are non-degradable in vivo. Additionally, the flow additives commonly used in SLS-sintered polymer powders are unsuitable for implantation into biodegradable polymer matrices. Commonly used flow additives include, but are not limited to, glass microspheres, carbon powder, pyrolytic silica, carbon nanotubes, and colorants.

[0005] While current SLS polymer materials are not suitable for use as biodegradable implants, several materials are available on the market for this purpose. These materials include, but are not limited to, polycaprolactone, polylactide, polylactic acid-co-glycolic acid, and various copolymers thereof. These materials are ideal for different medical applications depending on their mechanical, chemical, and degradation time requirements. For example, polydioxanone degrades at a much faster rate than polylactide; however, polylactide is significantly stronger than polydioxanone. Due to these properties, polylactide can be used in orthopedic applications, while polydioxanone can be used in blood contact applications such as arterial plugs.

[0006] Biodegradable polymers and SLS 3D printing are of great interest because SLS printing is a relatively rapid production method that can print large-volume parts in a single print, without the need for support materials, and manufacture 3D printed artifacts with high precision. This method can be used for applications of all sizes within the body. While SLS 3D printing can be used for a wide variety of applications, one manufacturing condition is not suitable for all materials. For example, the conditions typically used to print nylon cannot be used to print polycaprolactone. As a result, specialized printing methods will have to be developed. Using SLS-printed biodegradable medical polymers offers a biocompatible, biodegradable, and precision method for manufacturing implantable medical devices.

[0007] To develop biodegradable polymer SLS powders, the powder needs to be optimized by altering variables such as particle morphology and potentially adding flow additives. WO 2019 / 043137 A1 application specifies the use of unsintered amorphous hydroxyapatite at concentrations up to 10% by weight to improve powder flow. The use of water-soluble salts is beneficial because they will be removed by the body during implant degradation. As a result, no residual solids will remain at the implantation site after complete polymer implant degradation. Similar to WO 2019 / 043137 A1, water-soluble flow additives will benefit powder flowability, enabling printing using SLS technology. Invention Overview

[0009] On one hand, a manufacturing method is disclosed for producing polymer-based materials and polymer-based composites to be used in the production of blood-contact medical implants, which degrade without requiring removal and leave no residual material. The manufacturing method for producing polymer-based materials or polymer-based composites comprises, but is not limited to, impact milling, needle milling, shear milling, centrifugal milling, knife milling, cryogenic milling, mixed milling, impact milling, or air classifier milling. Additionally, blending methods such as drum blending, tumbling blending, cryogenic milling, mixed milling, impact milling, and especially high-shear blending are used to produce polymer-based powder composites. The mentioned materials can exist in blended powder form, sintered form, extruded form, or injection molded form. The polymer powder used in these compositions is a medical-grade bioabsorbable powder. Medical-grade powders may include, but are not limited to, polyvinyl alcohol, polyvinyl acetate, polylactide, polylactic acid-co-glycolic acid, polyglycolic acid, polycaprolactone, and especially polydioxanone. More specifically, the bioabsorbable powder used in medical devices comprises materials made from monomers including caprolactone, L-lactide, dL-lactide, glycolide, and p-dioxanone and mixtures thereof. As a result, this material can be used to produce implantable medical devices; furthermore, due to material degradation, removal surgery is unnecessary.

[0010] On the other hand, additives used in polymer powder composites are water-soluble salts. These water-soluble salts are embedded in the surface of polymer particles by methods including, but not limited to, drum blending, tumbling blending, cryogenic milling, mixed milling, impact milling, and especially high-shear blending. The water-soluble salts can also be embedded in the polymer particles during production. Water-soluble salts include, but are not limited to, non-toxic salts such as magnesium sulfate, sodium sulfate, potassium chloride, sodium chloride, sodium sulfate, potassium aluminum sulfate, magnesium chloride, and magnesium chloride hexahydrate. After implantation, as the polymer material degrades, the salts dissolve into the bloodstream and are removed in urine via the kidneys. Water-soluble salts, similar to other flow additives such as ceramics, do not remain within the implantation site; however, polymer powders with embedded water-soluble salts can be combined with other additives for specific materials. More specifically, additives such as bioceramics can be added to polymer powders with embedded water-soluble salts to produce powders specifically for use in orthopedic surgery.

[0011] On the other hand, water-soluble salts, after being blended or embedded on the surface of polymer powder particles, can benefit the flow of polymer powder in SLS printing. Water-soluble salts are believed to promote tumbling by reducing hydrogen bonds between particles, decreasing electrostatic charge between materials, creating surface changes on the particles, and thus benefiting the flow of polymer powder by helping to reduce water absorption levels. Polymer powders are highly complex materials that can change with slight variations in particle size, temperature, or humidity. A larger processing window can be achieved using flow aids or general additives.

[0012] On one hand, compositions of polymer-based material powders with suitable flow properties, thereby allowing for greater manufacturing simplicity and efficiency, are disclosed. Polymer powder composites are blended with additives at different concentrations, and then the flow is analyzed using dynamic flow analysis. The dynamic flow analysis methods used focus on the results of avalanche energy, fracture energy, and surface fractal. The lowest values ​​of these variables indicate the appropriate flow mechanism of the powder composition. Material composites intended for powder processing applications, more preferably laser sintering applications, are considered optimal if they have surface fractal results closest to 1 compared to other additive blends. Tap density and qualitative blade tests can also be used to evaluate the flow behavior of the material. Qualitative blade tests are performed for powder compositions intended for laser sintering or binder jetting applications, as the material will be used in such machines. After optimizing the flow of the composite powder, minimal mechanical force is required to bring the material into a loose state.

[0013] On the other hand, compositions of polymer-based material powders are disclosed that can be used in conjunction with selective laser sintering, spray-bonded powder molding, selective absorption sintering, and their mixing methods. The aforementioned processing methods require powders with good flowability regardless of ambient temperature. This ensures that the polymer powder produces a smooth surface for powder processing techniques to melt and produce 3D articles. If the powder has poor flowability, the powder surface may be porous and irregular, resulting in poor printed parts. Printed parts produced with powders having poor flowability can have unpredictable mechanical properties and high failure rates. Typical printing methods involve dispersing a powder layer on a platform, irradiating portions of the material corresponding to the cross-sectional geometry of the part, and then adding and irradiating additional layers until the part is complete.

[0014] On the other hand, compositions of polymer-based material powders are disclosed that can be used to produce structures with different internal and external geometries or uniform geometries. The developed polymer powders can be utilized in laser sintering applications, which allow 3D printing of complex geometries that are typically unattainable through conventional manufacturing methods. These geometries can be designed for specific loadings or for specific tissues such as trabecular bone structures. The geometry of the part varies according to its function.

[0015] In one aspect, a method for printing biodegradable polymer materials using laser sintering technology is disclosed. Specifically, the disclosed method for printing polymer powder composites includes printing a base anchoring layer. The base anchoring layer is irradiated with an energy density lower than that used to print the part. Energy density is a measurement of the energy imparted to the material powder bed by the laser during the printing operation. This value can be reported as J / mm². 3The thickness is calculated by dividing the laser wattage value by the product of the scanning speed, hatch distance, and layer height. Additionally, the base anchor layer can be thicker than 100 micrometers, particularly between 50 micrometers and 1 mm, more specifically 50 to 500 micrometers, and especially 50 to 300 micrometers. Printing the base anchor layer creates a surface anchored in the powder bed. After printing the base anchor layer, the machine begins printing the desired part; however, an initial layer of the part can be printed within the base anchor layer to further prevent curling, displacement, or geometric inaccuracies. Parts are typically printed at higher energy densities, and the base anchor layer prevents displacement, warping, curling, and shrinkage of the printed part. More specifically, the base anchor layer allows for the printing of fine details without displacement, warping, curling, and shrinkage. Without the printed base layer, most small details would fail to print. After printing is complete, the printed base layer can be removed from the printed part; furthermore, the printed base anchor layer can be partially separated into powder for future printing operations. The printed base anchor layer can be printed in multiple locations on the same part. For example, if a part has a thin overhang, an additional base anchoring layer will be printed in a powder bed before that part is irradiated in the method.

[0016] On the other hand, the geometry of the base anchoring layer will vary depending on the part being printed. The base anchoring layer can be thinner, thicker, wider, or narrower depending on the geometry of the part being printed.

[0017] In one aspect, an operator-optimizable annealing step is disclosed in a method following the printing of potential parts to define the crystallinity and mechanical properties of the final part. This aspect includes annealing polymer composite blends containing polydioxanone, possible additional polymers having melting points from 50°C to 240°C, and flow additives. The annealing method utilizes a processing temperature 10°C to 35°C below the melting point of the lowest polymer; furthermore, this temperature is maintained for a minimum of 1 second and a maximum of 8 hours before initiating a controlled cooling rate. The cooling rate is controlled at a rate from 0°C / min to 20°C / min. The annealing step is performed after the printing work has been completed. Additionally, the printing time can be included in the annealing time. Printed parts annealed for a longer time using a slower cooling rate tend to have higher yield tensile strength, higher modulus, and lower elongation at break. Printed parts annealed for a shorter time using a faster cooling rate have lower yield tensile strength, lower modulus, and higher elongation at break. Additionally, materials annealed for a longer time tend to have higher crystallinity. The operator can use this information to produce products with different mechanical properties and crystallinity depending on the application. For example, soft tissue applications may not require strong parts, but may require parts with high elongation; conversely, hard tissue applications may require strong parts with high modulus, rather than parts with high elongation.

[0018] On the one hand, the laser parameters used during laser sintering applications can alter the final mechanical properties and crystallinity of the printed parts. Energy density (J / mm²) 3 The calculation is performed by dividing the laser power (W) by the product of the scanning speed (mm / s), scanning gap (mm), and layer height (mm). At higher energy densities, the printed parts tend to be stronger until the mechanical property baseline is reached. Once the mechanical property baseline is reached, the yield tensile strength, modulus, and elongation at break become consistent. Higher energy densities tend to produce stronger parts than those produced using lower energy densities. Additionally, higher energy densities increase the crystallinity of the final part, while lower energy densities produce parts with lower crystallinity; however, annealing can produce similar crystallinity regardless of the energy density used to print the part. As a result, parts requiring higher strength can be printed at higher energy densities, while parts not requiring high strength can be printed at lower energy densities. Invention Details

[0020] 1. Definition

[0021] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In case of conflict, the definitions herein shall prevail. Preferred methods and materials are described below, although similar or equivalent methods and materials may be used in the implementation or testing of the invention. All publications, patent applications, patents, and other references mentioned herein are incorporated herein by reference in their entirety. The materials, methods, and examples disclosed herein are illustrative only and are not intended to be limiting.

[0022] As used herein, the terms “comprising,” “including,” “having,” “having,” “may,” “containing,” and variations thereof are intended as open-ended conjunctions, terms, or words that do not exclude the possibility of additional actions or structures. The singular forms “a,” “an,” and “the” include the plural referent unless the context clearly specifies otherwise. This disclosure also considers other embodiments that “contain the embodiments or elements proposed herein,” “comprise the embodiments or elements proposed herein,” and “consistently comprise the embodiments or elements proposed herein,” whether or not explicitly stated.

[0023] The conjunction "or" includes any and all combinations of one or more of the listed elements associated with it. For example, the phrase "an instrument containing A or B" could refer to an instrument that includes A but does not contain B, an instrument that includes B but does not contain A, or an instrument that contains both A and B. The phrase "at least one of A, B, ... and N" or "at least one of A, B, ... N, or combinations thereof" is defined in the broadest sense as meaning one or more elements selected from A, B, ... and N, that is, any combination of one or more of elements A, B, ... or N, including any single element or its combination with one or more of other elements, and may also include combinations of additional elements not listed.

[0024] The modifier “about” used with quantity includes the value being described and has the meaning prescribed by the context (e.g., it includes at least the degree of error associated with the measurement of the particular quantity). The modifier “about” should also be considered to disclose a range defined by the absolute values ​​of its two endpoints. For example, the expression “about 2 to about 4” also discloses the range “2 to 4”. The term “about” can refer to ±10% of the expressed number. For example, “about 10%” can indicate a range of 9% to 11%, and “about 1” can mean 0.9 to 1.1. Other meanings of “about” are obvious from the context, such as rounding, etc.; for example, “about 1” can also mean 0.5 to 1.4.

[0025] For the numerical ranges described in this article, each intermediate value with the same precision is explicitly included. For example, for the range of 6–9, the values ​​7 and 8 are included in addition to 6 and 9, and for the range of 6.0–7.0, the values ​​6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, and 7.0 are explicitly included.

[0026] The term "weight %" is used here as an abbreviation for weight percentage. It refers to the percentage of material by weight within the blend. "Weight %" should not be confused with an indication of blend homogeneity.

[0027] The terms “microencapsulated” and “encapsulated” are used herein to generally refer to bioactive agents incorporated into any kind of long-acting formulation or technology, regardless of shape or design; thus, “microencapsulated” or “encapsulated” bioactive agents may include bioactive agents incorporated into particles or microparticles, or they may include bioactive agents incorporated into solid implants, etc.

[0028] This document uses the term "bioactive agent" to include compounds of interest contained in or on a pharmaceutical formulation or dosage form for pharmaceutical or medical purposes to provide some form of therapeutic effect or to elicit some type of biological response or activity. "Bioactive agent" includes such a single agent and is also intended to include multiple bioactive agents, including, for example, combinations of two or more bioactive agents.

[0029] As used herein, “biocompatible” means a material that is generally non-toxic to the recipient and does not cause any significant adverse reactions in the subject, and furthermore, any metabolites or degradation products of the material are non-toxic to the subject. Typically, “biocompatible” substances do not cause clinically relevant tissue irritation, damage, toxicity, or immune responses in living tissue.

[0030] As used herein, the term "biodegradable" means a material that corrodes soluble substances or degrades under physiological conditions into smaller units or chemical substances that are themselves non-toxic (biocompatible) to the subject and can be metabolized, eliminated, or excreted by the subject.

[0031] As used herein, the term "water-soluble" refers to materials that are soluble in water, particularly those found in body tissues, bloodstream, etc. The term can also refer to materials that dissociate into ions upon exposure to an aqueous environment. Preferably, according to the invention, the term "water-soluble" refers to a salt having a solubility in water at 25°C of 5 mg / ml to 1500 mg / ml, more preferably 50 mg / ml to 1150 mg / ml, or 70 to 1000 mg / ml. Those skilled in the art know how to determine solubility, for example, by measuring conductivity. As reference values ​​for measurement, the following values ​​in water can be used: MgSO4 has a solubility of 351 mg / ml, magnesium sulfate heptahydrate has a solubility of 1130 mg / ml, sodium chloride has a solubility of 357 mg / ml, potassium chloride has a solubility of 340 mg / ml, anhydrous sodium sulfate has a solubility of 140 mg / ml, sodium sulfate heptahydrate has a solubility of 440 mg / ml, potassium dihydrogen phosphate has a solubility of 226 mg / ml, disodium hydrogen phosphate heptahydrate has a solubility of 118 mg / ml, and disodium hydrogen phosphate has a solubility of 77 mg / ml.

[0032] As used in this article, "non-agglomerated" refers to powders that do not produce large clumps of material due to the presence of moisture or the accumulation of powder.

[0033] As used herein, the terms "embedded" or "embedded" refer to something fixed to or embedded in a surface. An "embedded" article is an article that is fixed to or embedded in a surface by chemical, thermal, or physical integration methods.

[0034] The term "flow aid" refers to an additive that, when added to polymer-based powder materials, reduces the amount of agglomeration and the amount of energy required to cause powder avalanche or movement.

[0035] As used herein, “improved flowability” refers to the fluidization of powder particles through movement caused by various stimuli, including impact forces from falling particles, dynamic powder flow analysis, and, particularly, dispersion during processing via blades, rollers, or feed mechanisms. Improved flowability also refers to a reduction in fracture energy or avalanche energy after treatment of the base powder with flow aids.

[0036] As used herein, the terms "loose" and "loose state" refer to the physical state of powder when it is fluidized and uncompressed. In this state, the powder flows freely with minimal physical stimulation.

[0037] As used in this article, the term "powder processing technology" refers to, but is not limited to, technologies such as SLS 3D printing, powder fluidization, powder mixing, and powder feeding.

[0038] As used in this article, the term "avalanche energy" refers to the power change of the powder during an avalanche.

[0039] As used in this article, “fracture energy” refers to the energy generated during a powder avalanche.

[0040] As used herein, the term "interparticle friction" refers to the frictional force that exists between the surfaces of two contacting polymer particles. Additives reduce the contact surface area, which reduces the amount of interparticle friction and results in a more fluidized or more flowable powder.

[0041] As used in this article, the term "Hausnabi" refers to the ratio between the bulk density and tap density of a powder.

[0042] As used in this article, the term "compaction index" is a percentage of how much powder is compacted during a tap density measurement.

[0043] The polymer powder can be any biocompatible polymer. Biocompatible polymers include, but are not limited to, polyaryl ketones, polymethacrylates, polycarbonates, polyacetals, polyethylene, polypropylene, polylactide, polydioxanone, polycaprolactone, polyesteramide, polyurethane, polytrimethyl carbonate, polyglycolic acid, poly(amino acids), and copolymers of various monomers such as poly(lactide-copolymer-glycolic acid), poly(lactide-copolymer-caprolactone), poly(lactide-copolymer-trimethyl carbonate), poly(lactide-copolymer-polyethylene glycol), poly(orthoester), poly(phosphazene), poly(hydroxybutyrate), and those containing... Copolymers of poly(hydroxybutyrate), poly(lactide-co-caprolactone), polyanhydride, poly(dioxanone), poly(alkylene alkylates), copolymers of polyethylene glycol and polyorthoesters, biodegradable polyurethanes, polyamides, polyether esters, polyacetals, polycyanoacrylates, poly(ethylene oxide) / poly(propylene oxide) copolymers, polyketides, polyphosphates, polyhydroxyvalerates or copolymers containing polyhydroxyvalerates, polyalkylene oxalates, polyalkylene succinates, poly(maleic acid) and copolymers thereof, terpolymers, and combinations thereof.

[0044] Polymer powders can appear in many particulate forms due to their manufacturing methods. These forms include, but are not limited to, porous, hollow, solid, spherical, or irregular shapes.

[0045] Polymers based on lactide may contain any lactide residues, including all racemic and stereooriented forms of lactide, including but not limited to L-lactide, D-lactide, and D,L-lactide, or mixtures thereof. Available polymers containing lactide include, but are not limited to, poly(L-lactide), poly(D-lactide), and poly(DL-lactide); and poly(lactide-copolymer-glycolide), including poly(L-lactide-copolymer-glycolide), poly(D-lactide-copolymer-glycolide), and poly(DL-lactide-copolymer-glycolide); or copolymers, terpolymers, combinations, or blends thereof. L-lactide / glycolide polymers can be readily prepared by melt polymerization through ring-opening of lactide and glycolide monomers. Additionally, racemic DL-lactide, L-lactide, and D-lactide polymers are commercially available. L-polymers are more crystallizable and have slower reabsorption than DL-polymers. As a supplement to copolymers containing glycolide and DL-lactide or L-lactide, copolymers of L-lactide and DL-lactide are commercially available. Homopolymers of lactide or glycolide are also commercially available.

[0046] In a particular aspect, when the biodegradable polymer is poly(lactide-copolymer-glycolic acid) or any other copolymer (mentioned above), or a mixture of poly(lactide) and poly(glycolic acid), the amounts of lactide and glycolide in the polymer may vary. In another aspect, the biodegradable polymer contains 0 to 100 mol%, 40 to 100 mol%, 50 to 100 mol%, 60 to 100 mol%, 70 to 100 mol%, or 80 to 100 mol% lactide and 0 to 100 mol%, 0 to 60 mol%, 10 to 40 mol%, 20 to 40 mol%, or 30 to 40 mol% glycolide, wherein the amount of lactide and glycolide is 100 mol%. In another aspect, the biodegradable polymer can be poly(lactide), 95:5 poly(lactide-copolymer-glycolide), 85:15 poly(lactide-copolymer-glycolide), 75:25 poly(lactide-copolymer-glycolide), 65:35 poly(lactide-copolymer-glycolide), or 50:50 poly(lactide-copolymer-glycolide), where the ratio is a molar ratio.

[0047] On the other hand, the polymer can be poly(caprolactone) or poly(lactide-copolymer-caprolactone). Specifically, the polymer can be poly(lactide-caprolactone), which in various aspects can be 95:5 poly(lactide-copolymer-caprolactone), 85:15 poly(lactide-copolymer-glycolide), 75:25 poly(lactide-copolymer-caprolactone), 65:35 poly(lactide-copolymer-caprolactone), or 50:50 poly(lactide-copolymer-caprolactone), where the ratio is a molar ratio.

[0048] Flow aids and bioceramics include, but are not limited to, calcium sulfate and its doped variants (e.g., strontium, zinc, magnesium, fluorides, carbonates), calcium sulfate, calcium carbonate, and bioactive glasses such as bioglass. Calcium phosphate includes, but is not limited to, hydroxyapatite, tricalcium phosphate, hydroxyapatite containing calcium-poor carbonates, octacalcium phosphate, dicalcium phosphate, biphasic calcium phosphate, or mixtures thereof.

[0049] The term "water-soluble salt" as used herein refers to salts that dissociate into the ions they contain; additionally, salts are used as flow additives in the formation of SLS powders. Some salts referred to by the term "water-soluble salt" are magnesium sulfate, sodium sulfate, potassium chloride, sodium chloride, sodium sulfate, potassium aluminum sulfate, magnesium chloride, and magnesium chloride hexahydrate.

[0050] The term "bone guiding additive" refers to a material that can be added to a composition to enhance the bioresponse and bone tissue growth promotion of the disclosed composition; furthermore, the bone guiding additive can simultaneously act as a bioresponse promoter and the flow aid described above.

[0051] The term "composite material" refers to the use of flow aids, bioceramics, biomolecules, and / or bioactive agents that are mixed or processed with polymer-based materials.

[0052] The term "polymer-based material" refers to a material in which the largest component is a polymer.

[0053] The term "irradiation" refers to the act of introducing energy into a polymer material through various heat sources used during laser sintering applications. This includes CO2 lasers, blue light diodes, argon lasers, and so on.

[0054] On one hand, cryogenically milled polymer powders are used as the base powder. To improve their flow behavior, flow aids such as bioceramics must be added. Interestingly, particularly effective flow aids appear to share a common characteristic: a low-crystallinity (unsintered) form of bioceramics. This characteristic results in fairly uniform mixing behavior and good flow properties. Mixing with the polymer powder can be accomplished on a drum mixer or a high-shear mixer. These mixers are commercially available from Somakon and other companies.

[0055] Such flow aids are typically found in the range of 0.1 μm to 1 mm, 0.1 μm to 500 μm, 0.1 μm to 250 μm, 0.1 μm to 100 μm, or 0.1 μm to 50 μm, 0.1 μm to 40 μm, 0.1 μm to 30 μm, 0.1 μm to 20 μm, 0.1 μm to 5 μm, or 0.1 μm to 1 μm. Polymer composite blends have typical flow aid concentrations between 0.1 to 50 wt%, 0.1 to 40 wt%, 0.1 to 30 wt%, 0.1 to 20 wt%, 0.1 to 10 wt%, 0.1 to 5 wt%, 1 to 50 wt%, or 2 to 50 wt%. Furthermore, mixtures of different flow aids may be used, but the weight percentage of any single flow aid within the mixture shall not exceed the indicated total weight percentage of the total flow aid.

[0056] Such flow aids can be used for a variety of powder particle shapes. These shapes include irregularly shaped polymer powders and spherical polymer powders.

[0057] A wide variety of bioactive agents can be used in conjunction with the methods described herein. In one aspect, the bioactive agent can be a releasable bioactive agent, i.e., a bioactive agent that is released from a controlled release system into adjacent tissues or fluids of the subject. In other aspects, the bioactive agent can be located in or on a controlled release system.

[0058] Various forms of bioactive agents can be used, capable of being released from a controlled release system into adjacent tissues or fluids. For this purpose, liquid or solid bioactive agents can be incorporated into the controlled release systems described herein. The bioactive agents are at least very slightly soluble in water, and preferably moderately soluble. Bioactive agents may include salts of the active ingredient. Thus, bioactive agents can be acidic, basic, or amphoteric salts. They can be nonionic molecules, polar molecules, or molecular complexes capable of hydrogen bonding. Bioactive agents can be included in the composition, for example, in the form of uncharged molecules, molecular complexes, salts, ethers, esters, amides, polymeric drug conjugates, or other forms, thereby providing effective biological or physiological activity.

[0059] Examples of bioactive agents incorporated into this system include, but are not limited to, peptides, proteins such as hormones, enzymes, antibodies, etc., nucleic acids such as aptamers, iRNA, DNA, RNA, anti-transcriptional nucleic acids, etc., anti-transcriptional nucleic acid analogs, etc., low molecular weight compounds, or high molecular weight compounds. The bioactive agents covered for use in the disclosed implantable composite materials include anabolic agents, antacids, anti-asthmatic agents, anticholesterol and antilipidemic agents, anticoagulants, anticonvulsants, antidiarrheal agents, antiemetics, anti-infective agents including antibacterial and antimicrobial agents, anti-inflammatory agents, antimanic agents, antimetabolites, antiemetics, antitumor agents, antiobesity agents, antipyretics and analgesics, anticonvulsants, antithrombotic agents, antitussives, antiuric agents, antianginal agents, antihistamines (e.g., terfenadine), appetite suppressants, etc. Inhibitors, biological agents, brain dilators, coronary artery dilators, bronchodilators, cytotoxic agents, decongestants, diuretics, diagnostic agents, erythropoiesis agents, expectorants, gastrointestinal sedatives, hyperglycemic agents, hypnotics, hypoglycemic agents, immunomodulators, ion exchange resins, laxatives, mineral supplements, expectorants, neuromuscular drugs, peripheral neurolytic agents, psychotropic drugs, sedatives, stimulants, thyroid and antithyroid agents, tissue growth agents, uterine relaxants, vitamins, or antigenic materials.

[0060] Other bioactive agents include androgen inhibitors, polysaccharides, growth factors (e.g., vascular endothelial growth factor-VEGF), hormones, anti-angiogenic factors, dextromethorphan, dextromethorphan hydrobromide, noscapine, pentoxyverine citrate, chlorpheniramine hydrochloride, chlorpheniramine maleate, phenylindole tartrate, pyramine maleate, doxylamine succinate, bentoxamine citrate, norepinephrine hydrochloride, phenylpropanolamine hydrochloride, pseudoephedrine hydrochloride, ephedrine, codeine phosphate, codeine sulfate, morphine, mineral supplements, cholestyramine, N-acetylprocaine, acetaminophen, aspirin, ibuprofen, phenylpropanolamine hydrochloride, caffeine, guaiacol, aluminum hydroxide, magnesium hydroxide, peptides, polypeptides, proteins, amino acids, interferon, cytokines, and vaccines.

[0061] Representative drugs that can be used as bioactive agents include, but are not limited to, peptide drugs, protein drugs, desensitizing materials, antigens, anti-infective agents such as antibiotics, antimicrobial agents, antiviral agents, antibacterial agents, antiparasitic agents, antifungal agents and combinations thereof, anti-allergic agents, androgenic steroids, decongestants, hypnotics, steroidal anti-inflammatory agents, anticholinergics, sympathomimetic drugs, sedatives, miotics, psychostimulants, tranquilizers, vaccines, estrogens, fertility stimulants, humoral agents, prostaglandins, analgesics, antispasmodics, antimalarial agents, antihistamines, cardioactive agents, nonsteroidal anti-inflammatory agents, anti-Parkinson's agents, antihypertensive agents, β-adrenergic blockers, nutritional agents, and benzophenanthridine alkaloids. Reagents can also be substances that can act as stimulants, sedatives, hypnotics, analgesics, antispasmodics, etc.

[0062] Other bioactive agents include, but are not limited to, analgesics such as acetaminophen and acetylsalicylic acid; anesthetics such as lidocaine and serocaine; appetite suppressants such as dexthyroxine and benzodiazepine tartrate; anti-arthritis drugs such as methylprednisolone and ibuprofen; bronchodilators such as terbutaline sulfate, theophylline, and ephedrine; and antibiotics such as sulfamethoxazole, penicillin G, ampicillin, cephalosporins, amikacin, gentamicin, tetracycline, chloramphenicol, erythromycin, cloquinolones, isoniazid, and rifampin. Antifungal agents such as amphotericin B, nystatin, ketoconazole, etc.; antiviral agents such as acyclovir, amantadine, etc.; anticancer agents such as cyclophosphamide, methotrexate, etretinate, etc.; anticoagulants such as heparin, warfarin, etc.; anticonvulsants such as phenytoin sodium, diazepam, etc.; antidepressants such as isocarboxazid, amoxapine, etc.; antihistamines such as diphenhydramine hydrochloride, chlorpheniramine maleate, etc.; hormones such as insulin, progesterone, 17-α-hydroxy-hexanoate progesterone, iso-all-pregnanetanone testosterone (iso-al Prednisolone, dexamethasone, estrogen (e.g., estradiol), corticosteroids, glucocorticoids, androgens; sedatives such as thiamethoxam, diazepam, chlorpromazine hydrochloride, reserpine, nitrazepam hydrochloride; antispasmodics such as belladonna alkaloids, bicyclic amine hydrochloride; vitamins and minerals such as essential amino acids, calcium, iron, potassium, zinc, vitamin B12; cardiovascular drugs such as prazosin hydrochloride, nitroglycerin, propranolol hydrochloride, hydralazine hydrochloride, pancreatic lipase, succinate dehydrogenase; peptides and proteins such as LHRH, somatostatin, calcitonin, growth hormone, glucagon-like peptide, growth-releasing factor, angiotensin, FSH, EGF, bone blast protein (BMP), erythropoietin (EPO), interferon, interleukin, collagen, fibrinogen, insulin, factor VIII, factor IX. α-glucosidase, Vasopressin, ACTH, human serum albumin, gamma globulin, structural proteins, blood product proteins, complex proteins, enzymes, antibodies, monoclonal antibodies, etc.; prostaglandins; nucleic acids; carbohydrates; fats; anesthetics such as morphine, codeine, etc.; psychotropic drugs; antimalarial drugs, L-DOPA, diuretics such as furosemide, spironolactone, etc.; anti-ulcer drugs such as ranitidine hydrochloride, cimetidine hydrochloride, etc.; and calcium channel antagonists such as nimodipine, fenfluridine, silengiptide, 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors such as lovastatin, etc.

[0063] Biomolecules include, but are not limited to, fibrin, fibrinogen, cellulose, starch, collagen, and hyaluronic acid.

[0064] Characterization of different powders was performed on standard testing instruments, such as laser scattering instruments for particle size determination (available from Beckmann Coulter or Malvern). DSC tests were performed using a TA Instruments machine at a heating rate of 10 °C / min and a cooling rate of 20 °C / min. SEM was performed on a desktop machine (available from Hitachi). BET measurements were performed on a Micromeritics instrument.

[0065] Selective laser sintering (SLS) is performed on blade-based machines (such as the EOS P series). This technology manufactures physical parts by selectively solidifying various fine powders. SLS uses powder to build parts layer by layer, with the powder selectively bonded as a laser beam scans the powder across the cross-sectional area of ​​each layer. Typical laser energy density is 7 kJ / m² anywhere. 2 -60kJ / m 2 SLS melting utilizes a thin layer of powder (typically ~0.1 mm thick) dispersed across the fabrication area using a blade. Part fabrication occurs inside a closed chamber filled with an inert gas, preferably nitrogen, to minimize oxidation and degradation of the powder material. The powder in the fabrication platform is maintained at an elevated temperature slightly below the melting point of the powder material (only for semi-crystalline polymers).

[0066] Qualitative methods for characterizing powder flowability involve the use of flowability testing instruments (Mercury Scientific Instruments) consisting of a rotating cylindrical drum with glass walls, which uses a camera to characterize the movement of powder particles. The instrument measures the maximum height of the powder pile before an avalanche occurs. If the powder height is high before the avalanche, the powder requires more energy to flow. It is an indicator of the minimum energy required to make the powder particles flow. Unless otherwise mentioned, the test is conducted under ambient conditions (rt, approximately 40% humidity level).

[0067] According to United States Pharmacopeia 36 (USP) <429> Particle size is determined according to Chapter 7.0 (EP) 2.9.31 of the European Pharmacopoeia. Particle size distribution is determined using a laser diffraction instrument (e.g., Fa. Sympatec GmbH, HELOS type equipped with a RODOS dry dispersion device). Laser diffraction methods are based on the phenomenon that particles scatter light in all directions, and the intensity pattern depends on the particle size. A representative sample, dispersed at an appropriate concentration in a suitable liquid or gas, is passed through a beam of light, typically from a monochromatic light source from a laser. The light scattered by the particles at various angles is measured by a multi-element detector, and the numerical values ​​associated with the scattering pattern are recorded for subsequent analysis. The numerical scattering values ​​are then transformed using appropriate optical models and mathematical procedures to derive the ratio of the total volume to the discrete number of size classes forming the volumetric particle size distribution (e.g., d0). 50 Describes the particle diameter corresponding to the 50% cumulative undersize distribution.

[0068] 2. Inventive Composition

[0069] This document discloses compositions of polymeric materials suitable for use in the production of medical devices and / or the surface treatment of medical devices.

[0070] This article also discloses compositions of polymeric materials suitable for use in the production of food contact devices or surfaces.

[0071] This article also discloses compositions of polymeric materials suitable for use in powder processing technologies such as selective laser sintering, spray-bonded powder forming, selective absorption sintering, and their mixing methods.

[0072] This article also discloses compositions comprising polymeric materials and flow aids of varying concentrations to improve material flow during processing.

[0073] This article also discloses compositions comprising polymer materials and water-soluble salts of varying concentrations to facilitate the flow of polymer particles and to induce or inhibit biological reactions caused by pores created by the extraction of water-soluble salts.

[0074] This article also discloses compositions comprising polymer materials and water-soluble salts of varying concentrations to facilitate the flow of polymer particles for various powder processing technologies.

[0075] This article also discloses compositions comprising polymeric materials and bioceramics of varying concentrations to induce or inhibit biological responses and / or improve material flow during processing.

[0076] This article also discloses compositions comprising polymeric materials and varying concentrations of biomolecules to induce or inhibit biological responses and / or improve material flow during processing.

[0077] This article also discloses compositions comprising polymeric materials and bioactive agents of varying concentrations to induce or inhibit biological reactions and / or improve material flow during processing.

[0078] This article also discloses compositions comprising polymeric materials and flow aids, bioceramics, biomolecules, bone-guiding additives, water-soluble salts and / or bioactive agents at varying concentrations to improve the bulk density of a base powder formulation.

[0079] This article also discloses compositions comprising polymeric materials and water-soluble salts of varying concentrations to improve the bulk density of a base powder formulation.

[0080] This article also discloses compositions comprising polymer materials and flow aids, bioceramics, biomolecules, bone guiding additives, water-soluble salts and / or bioactive agents at different concentrations, which have different part densities depending on the processing parameters when processed using various powder processing techniques.

[0081] This article also discloses compositions comprising polymer materials and water-soluble salts of varying concentrations, which, when processed using various powder processing techniques, have different part densities depending on the processing parameters.

[0082] This article also discloses compositions comprising polymer materials and water-soluble salts of varying concentrations, wherein the salts are used to obtain specific mechanical properties of articles prepared from composite powders, depending on the selected weight percentages of water-soluble oxygen and salt.

[0083] This article also discloses compositions comprising polymeric materials that are mixed with flow aids of varying concentrations, water-soluble salts, bioceramics, biomolecules, bone-guiding additives, and / or bioactive agents and processed into articles.

[0084] This article also discloses compositions comprising polymeric materials that are mixed with water-soluble salts of varying concentrations and processed into articles.

[0085] This article also discloses compositions comprising polymeric material composite blends for producing articles with different geometries on internal and external surfaces.

[0086] This article also discloses compositions comprising polymeric material composite blends for the production of articles that are biodegradable, biocompatible, and / or both.

[0087] This article also discloses compositions comprising polymeric material composite blends for producing articles in which composite additives can be removed after manufacturing.

[0088] This document also discloses polymer-based composite materials, wherein the polymer material comprises 0% by weight to about 100% by weight of the composition, for example, 1% by weight to about 100% by weight of the composition, for example, 5% by weight to about 100% by weight of the composition, for example, 10% by weight to about 100% by weight of the composition, for example, 20% by weight to about 100% by weight of the composition, for example, 30% by weight to about 100% by weight of the composition, for example, 40% by weight to about 100% by weight of the composition, for example, 50% by weight to about 100% by weight of the composition, for example, about 60% by weight to about 100% by weight of the composition, for example, about 70% by weight to about 100% by weight of the composition, for example, 80% by weight to about 100% by weight of the composition, for example, 85% by weight to about 100% by weight of the composition, for example, 90% by weight to about 100% by weight of the composition, for example, 95% by weight to about 100% by weight of the composition. Polymer materials can be essentially composed of polyesters, including polydioxanone, polycaprolactone, polylactide, polylactic acid-co-glycolic acid, polyglycolic acid, polyvinyl acetate, polyvinyl alcohol, and blends thereof.

[0089] This article also discloses polymer-based composite materials, wherein the polymer material can be polyaryl ketone, polymethacrylate, polycarbonate, polyacetal, polyethylene, polypropylene, polylactide, polydioxanone, polycaprolactone, polyesteramide, polyurethane, polytrimethyl carbonate, polyglycolic acid, poly(amino acid), and copolymers of various monomers such as poly(lactide-copolymer-glycolic acid), poly(lactide-copolymer-caprolactone), poly(lactide-copolymer-trimethyl carbonate), poly(lactide-copolymer-polyethylene glycol), poly(orthoester), poly(phosphazene), and poly(hydroxyl group). Butyrate, copolymers containing poly(hydroxybutyrate), poly(lactide-co-caprolactone), polyanhydride, poly(dioxanone), poly(alkylene alkylates), copolymers of polyethylene glycol and polyorthoesters, biodegradable polyurethanes, polyamides, polyether esters, polyacetals, polycyanoacrylates, poly(ethylene oxide) / poly(propylene oxide) copolymers, polyketides, polyphosphates, polyhydroxyvalerates or copolymers containing polyhydroxyvalerates, polyalkylene oxalates, polyalkylene succinates, poly(maleic acid) and copolymers thereof, terpolymers, and combinations thereof.

[0090] This article also discloses polymer-based composite materials in which polydioxanone, polylactide, polyglycolic acid, or polycaprolactone powders can be blended with other polymeric materials, such as polyaryl ketones, polymethacrylates, polycarbonates, polyacetals, polyethylene, polypropylene, polylactide, polydioxanone, polycaprolactone, polyesteramide, polyurethane, polytrimethyl carbonate, polyglycolic acid, and copolymers of various monomers, such as poly(lactide-copolymer-glycolic acid), poly(lactide-copolymer-caprolactone), poly(lactide-copolymer-trimethyl carbonate), and poly(lactide-copolymer-polyethylene glycol). Poly(orthoester), poly(phosphazene), poly(hydroxybutyrate), copolymers containing poly(hydroxybutyrate), poly(lactide-co-caprolactone), polyanhydride, poly(dioxanone), poly(alkylene alkylates), copolymers of polyethylene glycol and polyorthoester, biodegradable polyurethane, polyamide, polyether ester, polyacetal, polycyanoacrylate, poly(ethylene oxide) / poly(propylene oxide) copolymer, polyketide, polyphosphate, polyhydroxyvalerate or copolymers containing polyhydroxyvalerate, polyalkylene oxalate, polyalkylene succinate, poly(maleic acid) and copolymers thereof, terpolymers, combinations.

[0091] This document also discloses polymer-based composite materials in which bone-guiding additives, flow aids, bioceramics, biomolecules and / or bioactive agents constitute 0% to 99% by weight of the composition, for example, 0% to 97% by weight of the composition, for example, 0% to 95% by weight of the composition, for example, 0% to 95% by weight of the composition, for example, 0% to 90% by weight of the composition, for example, 0% to 80% by weight of the composition, for example, 0% to 70% by weight of the composition, for example, 0% to 60% by weight of the composition, for example, 0% to 50% by weight of the composition, for example, 0% to 40% by weight of the composition, for example, 0% to 30% by weight of the composition, for example, 0% to 20% by weight of the composition, for example, 0% to 10% by weight of the composition, for example, 0% by weight of the composition. % to 5 wt%, for example, 0.5 wt% to 99 wt% of the composition, for example, 0.5 wt% to 97 wt% of the composition, for example, 0.5 wt% to 95 wt% of the composition, for example, 0.5 wt% to 95 wt% of the composition, for example, 0.5 wt% to 90 wt% of the composition, for example, 0.5 wt% to 80 wt% of the composition, for example, 0.5 wt% to 70 wt% of the composition, for example, 0.5 wt% to 60 wt% of the composition, for example, 0.5 wt% to 50 wt% of the composition, for example, 0.5 wt% to 40 wt% of the composition, for example, 0.5 wt% to 30 wt% of the composition, for example, 0.5 wt% to 20 wt% of the composition, for example, 0.5 wt% to 10 wt% of the composition, and / or for example, 0.5 wt% to 5 wt% of the composition.

[0092] This article also discloses polymer-based composites in which bone-guiding additives, flow aids, bioceramics, biomolecules and / or bioactive agents may constitute at least 99%, at least 95%, at least 90%, at least 80%, at least 70%, at least 60%, at least 50%, at least 40%, at least 30%, at least 20%, at least 10%, or at least 5% by weight of the final composite.

[0093] This article also discloses polymer-based composites wherein a water-soluble salt may comprise at least 99%, at least 95%, at least 90%, at least 80%, at least 70%, at least 60%, at least 50%, at least 40%, at least 30%, at least 20%, at least 10%, or at least 5% by weight of the final composite.

[0094] This document also discloses polymer-based composite materials in which bone-guiding additives, flow aids, bioceramics, biomolecules and / or bioactive agents may have diameters of not more than 250 micrometers, not more than 200 micrometers, not more than 150 micrometers, not more than 100 micrometers, not more than 75 micrometers, not more than 55 micrometers, not more than 50 micrometers, not more than 25 micrometers, not more than 15 micrometers, not more than 10 micrometers, not more than 5 micrometers, about 0.1 micrometers to about 250 micrometers, about 0.1 micrometers to about 200 micrometers, about 0.1 micrometers to about 150 micrometers, about 0.1 micrometers to about 100 micrometers, about 0.1 micrometers to about 75 micrometers, about 0.1 micrometers to about 55 micrometers, about 0.1 micrometers to about 50 micrometers, about 0.1 micrometers to about 25 micrometers, about 0.1 micrometers to about 10 micrometers, and about 0.1 micrometers to about 5 micrometers.

[0095] 3. Invented manufacturing method

[0096] It should be understood that the methods for preparing the compositions disclosed below are not exhaustive and that methods may be combined or modified to suit any of the compositions mentioned above that have been disclosed.

[0097] This document discloses methods for manufacturing, preparing, and processing polymer-based materials as previously described. The polymer-based materials, polydioxanone, polycaprolactone, polyglycolic acid, and polylactide, can be blended with various concentrations of bone-guiding additives, flow aids, bioceramics, biomolecules, water-soluble salts, and / or bioactive agents by a variety of methods prior to processing using a variety of possible powder processing techniques.

[0098] On the one hand, polymer-based composite powders can be processed using selective laser sintering, spray adhesive powder forming, selective absorption sintering, and their mixing methods.

[0099] On the other hand, polymer-based materials, bone-guiding additives, flow aids, bioceramics, biomolecules, water-soluble salts and / or bioactive agent powders are produced by grinding methods such as jet milling, impact milling, centrifugal milling, needle milling, knife milling, cryogenic milling, mixed milling, impact milling, air classifier milling and their mixing methods.

[0100] On the other hand, polymer-based materials are used, but not limited to, high-shear mixing, tumbling blending, solvent blending, and other mixing methods with bone-guiding additives, flow aids, bioceramics, biomolecules, water-soluble salts, and / or bioactive agents.

[0101] On the other hand, polymer-based materials are blended with water-soluble salts using high-shear mixing, tumbling blending, solvent blending, and other mixing methods.

[0102] On the other hand, polymer-based materials are blended with water-soluble salts using a combination of high-shear mixing, tumbling blending, solvent blending, jet milling, impact milling, centrifugal milling, pin milling, knife milling, cryogenic milling, mixed milling, impact milling, wind classifier milling, and other mixing methods.

[0103] On the other hand, polymer-based materials are blended with water-soluble salts using abrasive media of varying sizes and at wide temperature ranges within a co-milling manufacturing method. The abrasive media are medical-grade stainless steel materials in various shapes, with dimensions varying from 1mm to 100mm, 1mm to 90mm, 1mm to 80mm, 1mm to 70mm, 1mm to 60mm, 1mm to 50mm, 1mm to 40mm, 1mm to 30mm, 1mm to 20mm, 1mm to 10mm, or 1mm to 5mm. Furthermore, the co-milling temperature range is from the melting temperature of the polymer material to low-temperature conditions.

[0104] On the other hand, polymer-based materials are blended with a second high-modulus polymer, such as polyethylene glycol (PEG) and polyvinyl alcohol (PVA), using abrasive media of varying sizes and over a wide temperature range in a co-milling manufacturing method. The abrasive media are medical-grade stainless steel materials in various shapes, with dimensions varying from 1 mm to 100 mm, 1 mm to 90 mm, 1 mm to 80 mm, 1 mm to 70 mm, 1 mm to 60 mm, 1 mm to 50 mm, 1 mm to 40 mm, 1 mm to 30 mm, 1 mm to 20 mm, 1 mm to 10 mm, or 1 mm to 5 mm. Furthermore, the co-milling temperature range can be from the melting temperature of the polymer material to low-temperature conditions.

[0105] On the other hand, polymer-based materials blended with bone-guiding additives, flow aids, bioceramics, biomolecules, and / or bioactive agents can be used in melt processing techniques such as, but not limited to, single-screw extrusion, twin-screw extrusion, injection molding, compression molding, and electrospinning. The resulting blends and processed materials form composite materials.

[0106] On the other hand, polymer-based materials blended with water-soluble salts can be used in melt processing technologies such as single-screw extrusion, twin-screw extrusion, injection molding, compression molding, electrospinning, 3D printing, or a combination thereof.

[0107] On the other hand, polymer-based composites can be granulated, pelletized, or extruded into raw material shapes for other applications.

[0108] On the other hand, polymer-based composite powders are prepared for processing by a drying method, which may or may not utilize temperatures within approximately 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 10°C, 20°C, 30°C, 40°C, 50°C, and 60°C of the polymer's melting temperature.

[0109] On the other hand, polymer-based composite powders are prepared for processing by a drying method, which may or may not utilize a vacuum.

[0110] On the other hand, polymer-based composite powders are prepared for processing by a drying method, which may or may not involve an annealing step for the polymer material.

[0111] On the other hand, polymer-based composite powders are prepared for processing by a drying method, which may or may not prepare materials for processing using powder processing technology, wherein the drying method increases the melting initiation point of the polymer material.

[0112] On the other hand, polymer-based composite powders are processed using powder processing techniques such as selective laser sintering, spray-bonded powder forming, selective absorption sintering, and their mixing methods, in which the printed article can be cooled at a slow rate within the machine to allow the article to be annealed.

[0113] On the other hand, blending water-soluble salts using conventional blending methods is unsuitable because it does not adhere to the surface of polymer particles or provide any benefit to the powder flow. When incorporating water-soluble salts into polymer powders, high-shear blending and drum blending do not result in a uniform distribution of the salt additive on the polymer particle surface. Furthermore, grinding the salt to a submicron particle size prior to the blending operation is detrimental to salt adhesion to the polymer particle surface. Instead, a co-milling method can be used to easily embed uncrushed salt and polymer particles at room temperature or low temperatures. The co-milling method utilizes the effect of the grinding media to embed the salt additive into the surface of the polymer particles.

[0114] 4. Example

[0115] The following examples are provided to provide those skilled in the art with a complete disclosure and description of how to prepare and evaluate the compounds, compositions, articles, apparatus, and / or methods claimed herein, and are intended merely as examples of the invention and not to limit the scope of what the inventors consider to be their invention. Efforts have been made to ensure accuracy regarding numerical values ​​(e.g., amounts, temperatures, etc.), but some errors and deviations should be accounted for. Unless otherwise indicated, parts are parts by weight, temperatures are in °C or at ambient temperature, and pressures are at or near atmospheric pressure.

[0116] Example 1

[0117] Grinding

[0118] Composite powders are produced by blending two types of ground powders. The polydioxanone polymer used to produce the powder composite is ground after the raw materials are procured. The grinding process for polydioxanone requires a cryogenic grinding method. The polydioxanone particles fed into the cryogenic grinding method have a particle size of 1 to 3 mm and a bulk density of 0.62 kg / L. After grinding, the polydioxanone powder material has 90% of the powder having a particle size of less than 100 micrometers and a powder bulk density of 0.41 kg / L. The particle size of the ground polydioxanone polymer, as measured using laser diffraction, is shown in Table 1. All lumps are removed from the polydioxanone powder before blending with additives or before use in powder processing techniques.

[0119] Table 1. Particle size measurement results of ground polydioxanone powder by laser diffraction.

[0120] 12 44 109

[0121] Milling is far more efficient than emulsification or other solvent-based methods for producing polydioxanone powder. Polydioxanone requires highly corrosive and toxic solvents for dissolution, such as hexafluoro-2-propanol (HFIP). Following emulsification, the solvent must be removed to a level safe for implantation. As a result, while emulsification can produce particles within a suitable size range for laser sintering applications, it is not recommended for polydioxanone.

[0122] Further polymer powders are produced from polycaprolactone and polylactide according to WO 2019 / 043137 A1. Particle sizes smaller than 100 micrometers can be achieved. The particle sizes of the polycaprolactone and polylactide milled polymers obtained using a method similar to that of polydioxanone are shown in Table 2.

[0123] Table 2. Particle size measurement results of ground polycaprolactone and polylactide polymer powders by laser diffraction.

[0124] Polycaprolactone 21 53 103 Polylactide 28 68 109

[0125] Example 2

[0126] Flow with additives

[0127] Various compositions were prepared, comprising polydioxanone powder and additives. The additives can vary depending on the application; furthermore, multiple additives can be blended together to create multifunctional powder composites. The additives discussed in this example can be categorized as bone-guided additives, bioglass, and bioceramics. The flow of each composition was evaluated using a dynamic flow analysis method with a rotating powder analyzer from Mercury Scientific. 40 mL of each powder composition was used for testing at 90°C. This temperature was chosen because it is close to the possible printing temperature used during laser sintering. Three parameters available for developing flowable powders for powder manufacturing technologies are avalanche energy, fracture energy, and surface fractal as defined above. Flow results from baseline polydioxanone powder are shown in Table 3.

[0128] Table 3. Flow behavior of pure polydioxanone powder at 90℃

[0129]

[0130] Dynamic flow analysis of pure polydioxanone (POD) indicates that the powder flow is unsuitable for SLS or similar laser sintering methods due to the powder surface having a surface fractal of 9.77. Once the additives are blended with the POD powder, the surface fractal decreases rapidly. A polymer surface fractal of less than 2 is desired, with the best result being 1. This indicates that the powder produces a smooth surface after avalanche or displacement within the material. SLS methods requiring smooth powder surfaces will necessitate powders with a surface fractal as close to 1 as possible; however, this may not be necessary for material delivery techniques, as the smoothness of the powder surface will not affect processing. For powder processing techniques requiring material flow suitable for consistent material distribution, powder compositions with the lowest fracture and avalanche energies should be selected. POD powder blends with additives are shown in Table 4. For all additives, their particle size is mentioned. The term "submicron" indicates an additive with a particle size less than 2 micrometers. The term "10 micrometers" indicates an additive with an average particle size of 10 micrometers.

[0131] Table 4. Pure polydioxanone powder and submicron UHA (D) at 90℃ 50 Flow behavior (700-900nm)

[0132] Avalanche energy (kJ / kg) 29.4 17.13 16.11 16.46 20.75 Fracture energy (kJ / kg) 100.83 88.64 95.92 100.99 110.05 Surface fractals 2.16 1.79 2.08 2.28 2.9

[0133] Flow results for blends of submicron unsintered hydroxyapatite (submicron UHA) with different particle sizes showed that the best flow outcome was achieved with a 3 wt% additive. This additive concentration exhibited the lowest surface fractal, the lowest fracture energy, and the third lowest avalanche energy. Qualitative blade testing was performed by placing blends of 3 wt% and 5 wt% submicron UHA and polydioxanone powders in a selective laser sintering machine, allowing the blade to produce a smooth surface, dropping the platform 100 microns, adding more composite powder blends, and then allowing the blade to distribute 100 micron layers. If the powder surface was smooth and free of lumps, this was considered acceptable for 3D printing applications. The 5 wt% submicron UHA and polydioxanone powder blend showed the best blade test results and should be selected for selective laser sintering printing parameter development. The unsintered hydroxyapatite was obtained from Himed.

[0134] Table 5. Pure polydioxanone powder and D at 90℃ 50 Flow behavior of 10-micron UHA

[0135] Avalanche energy (kJ / kg) 28.14 21.01 22.4 25.14 32.57 Fracture energy (kJ / kg) 94.99 98.31 101.65 112.36 116.96 Surface fractals 2.04 1.8 2.45 2.68 3.47

[0136] Compared to submicron unsintered hydroxyapatite, 10-micron unsintered hydroxyapatite exhibits higher avalanche and fracture energies (Table 5). This indicates that more energy is required to induce the loose state of the powder to flow. Qualitative blade testing was performed on a blend of 3 wt% 10-micron UHA and polydioxanone powder, demonstrating its suitability for selective laser sintering (SLS). SLS printing parameter development for this blend should begin with 3 wt% 10-micron UHA.

[0137] Table 6. Flow behavior of pure polydioxanone powder and unsintered FHA at 90℃

[0138] Avalanche energy (kJ / kg) 46.16 30.69 16.64 11.67 12.61 Fracture energy (kJ / kg) 136.49 87.02 80.87 80.54 86.86 Surface fractals 5 2.02 1.94 1.76 1.91

[0139] Submicron unsintered fluorapatite (submicron unsintered FHA) is a fluorine-doped apatite that can be used as a bone-guiding additive and flow aid. Flow results from blends of polydioxanone and submicron unsintered FHA indicate that the optimal additive concentration for selective laser sintering is 7% by weight. (Table 6)

[0140] Table 7. Flow behavior of pure polydioxanone powder and submicron bioglass at 90℃

[0141]

[0142]

[0143] Submicron bioglass does not indicate it will be a good flow agent at loadings of 1–10 wt%, but it can be blended with other flow additives mentioned in the bone-specific blends. Furthermore, when surface fractals are plotted with additive concentrations, the trend line equation shows that a surface fractal of 2 can be achieved with 21.5 wt% bioglass. This indicates that bioglass can be used as a flow aid at higher concentrations. Bioglass was obtained from Schott (Table 7).

[0144] Table 8. Flow behavior of pure polydioxanone powder and submicron UTCP at 90℃

[0145] Avalanche energy (kJ / kg) 47.28 24.62 19.45 15.18 16.86 Fracture energy (kJ / kg) 105.21 86.33 86.94 88.63 93.08 Surface fractals 2.46 1.96 1.98 1.95 2.21

[0146] Submicron unsintered tricalcium phosphate (submicron UTCP) has proven to be a good flow reagent in the range of 1–10 wt%, with concentrations between 3–7 wt% being acceptable for selective laser sintering. Submicron UTCP is obtained from Himed.

[0147] Example 3

[0148] Preparation of composite materials

[0149] The composite powders have different mechanical properties depending on the additives used, as shown in Table 9. Polydioxanone (… Blends of X 206S powder with bioglass containing silane as a surface treatment exhibit the highest mechanical strength, blends of polydioxanone powder with unsintered FHA exhibit the highest modulus, and blends of polydioxanone powder with 10-micron UHA exhibit the highest elongation at break (Table 9). These results suggest that additives selected as flow aids can also be used to induce a mechanical response in the final product manufactured from powder composite blends. The stretch strips produced by injection molding have a geometry similar to that of shape ISO 20753 A14.

[0150] Table 9 Mechanical properties of injection-molded polydioxanone powder with various additives

[0151]

[0152] Example 4

[0153] DSC, Annealing

[0154] The crystallinity of the composite powder can be controlled by the operator before or after printing. This process can be described, but is not limited to, the terms annealing, tempering, toughening, strengthening, and hardening. For all annealing tests, a processing temperature of 98°C was used for the composite PDO + 3 wt% 10 micron UHA. The cooling rate of the annealing method was controlled between 2.5°C and 10°C. The unprocessed composite powder had a crystallinity of 57.6%, while the processed powder had a crystallinity of 56.3%. The processed composite powder was cooled overnight in a Formiga P110 SLS machine from the processing temperature of 98°C at a rate of less than 2°C / min. The crystallinity of the polymer powder observed at a cooling rate of 2.5°C / min was 57.25%, while the crystallinity of the polymer powder observed at a cooling rate of 10°C / min was 59.32%. The maximum crystallinity of the polymer powder observed at 5°C / min was 62.18%. The crystallinity data for the annealing tests are shown in Table 10.

[0155] Besides changes in crystallinity, the annealing process also affects the melting initiation point of the polymer powder. Each material with a controlled cooling rate has a melting initiation point of at least 98°C. The melting initiation point is highest at 99.21°C for materials cooled at 2.5°C / min, while materials cooled at 5°C / min and 10°C / min have a melting initiation point of 98.97°C. Furthermore, unprocessed materials and materials processed without controlled cooling have much lower melting initiation points of 92.16°C and 94.46°C, respectively. This indicates that annealing or controlled cooling of the material after processing can be beneficial for the processing of PDO composite powders. Higher processing temperatures prevent material curling or displacement during the printing process. This results in a higher print job success rate.

[0156] Table 10 Crystallinity of powders annealed at different cooling rates

[0157] Unprocessed powder 57.60 92.16 Processing powder 56.25 93.46 Cooling at 2.5℃ / min 57.27 99.21 Cooling at 5℃ / min 62.18 98.97 Cooling at 10℃ / min 59.32 98.97

[0158] Example 5

[0159] Preparation method for SLS processing-blending

[0160] Polydioxanone (POD) composite powder blends were prepared by mixing milled POD powder with various possible additives at different concentrations. The POD powder and additives were weighed under laboratory conditions using a balance accurate to 1 mg. The POD powder and additives were then placed in a Somakon MP-LB Labormischer Speedmix and mixed three times at 300 rpm for 2 minutes each time. The mixing container volume was 0.5 L. A tumbling mix can also be used to blend the POD powder and additives, but this process takes significantly longer.

[0161] Example 6

[0162] Preparation method for SLS processing-hybrid grinding

[0163] A mixing and milling process was developed by placing 5 grams of polymer particles and 0.26 grams of salt in a container with 25 mm stainless steel balls. The container was vibrated at a frequency of 30 Hz for three minutes. After this mixing and milling process, the salt was embedded in the surface of the polymer particles in a uniform distribution. Furthermore, no salt additive was observed on the imaging platform, indicating that a uniform powder blend was obtained.

[0164] Example 7

[0165] Improving polymer powder flowability with water-soluble salt flow aids

[0166] Three polymer powders were blended with water-soluble salts, and their powder flow was evaluated at elevated temperatures. X 206S (polydioxanone), C 212 (polycaprolactone) and The L207S polymer was ground and sieved until all collected material was less than 100 μm in size. Three polymers were mixed and ground, with 5 g of polymer powder and 0.26 g of salt additive added to achieve a salt-to-polymer powder concentration of 5% by weight. All materials were placed in a stainless steel container with 25 mm stainless steel balls and vibrated at 30 Hz for 3 minutes. Dynamic flow analysis was used to evaluate the resulting base powder and powder blends to determine the effect of water-soluble salts on powder flow. All base powders showed benefits in powder flow after being mixed and ground with water-soluble salts.

[0167] Table 11 Salts with different water soluble concentrations at 160℃ L 207 S Flow Properties

[0168]

[0169] Table 12 Salts with different water soluble concentrations at 50℃ C 212 Flow Properties

[0170]

[0171] Table 13 Salts with different water soluble concentrations at 90℃ X 206 S Flow Properties

[0172]

[0173] Example 8

[0174] use Powder flow optimization of X 206 S

[0175] Using multiple salt concentrations and X 206 S was used to evaluate the use of water-soluble salts to improve the flowability of polymer powder. Water-soluble salts were mixed and milled with polymer powder at concentrations of 1, 5, and 10% by weight using the mixing and milling method determined in Example 6. The use of different concentrations showed that while each salt was beneficial to the flowability of the polymer powder, the concentration of each salt used would vary depending on the desired flowability.

[0176] Table 14 Salts with different water soluble concentrations at 160℃ L 207 S Flow Properties

[0177]

[0178] Table 15 Salts with different water soluble concentrations at 50℃ C 212 Flow Properties

[0179]

[0180] Table 16 Salts with different water soluble concentrations at 90℃ X 206S Flow Properties

[0181]

[0182] Example 9

[0183] Processing methods

[0184] The disclosed composite powder processing steps can be optimized to obtain the desired crystallinity of the printed article. The flow of PDO composite powder containing 3 wt% 10 microns of unsintered calcium phosphate is sufficient for the printing method up to 105°C in the printing chamber. As a result, the recommended printing chamber temperature range is 95°C to 100°C, more preferably 98°C + / - 1.5°C. After reaching 98°C, all material is heated in a Formiga P110 SLS machine for at least 1 hour to ensure the material temperature remains at 98°C; furthermore, the layer height (L) of the printing method is set to 100 microns (0.1 mm). The printing parameters that are varied for each printing setting are laser wattage (W), scanning speed (S), and scanning gap (D). The printing energy density is determined using the printing parameters and layer height. The energy density formula used is shown in Equation 1.

[0185] Equation 1 Energy density equation

[0186]

[0187] Before printing the part, use 0.15J / mm3 Energy density printing is performed on a base carrier with dimensions of 300 × 75 × 0.3 mm. Stretch strips are then printed on a second base carrier. Prior to the third layer on the base carrier, only the cross-section corresponding to the geometry of the stretch strip is irradiated by laser. Stretch strips are printed at a series of different energy densities.

[0188] As the printing energy density increases, the crystallinity of the resulting printed articles increases. All printed articles, designated as "unannealed," were immediately removed from the printing chamber after the printing job. The unannealed printed articles showed a crystallinity increase from 41.71% at 0.15 J / mm³ to 47.31% at 0.3 J / mm³. Furthermore, after annealing the printed articles by cooling them in a Formiga P110 SLS machine at a rate of less than 2 °C / min, the crystallinity at an energy density of 0.25 J / mm³ increased to 48.14%. As a result, the energy density of the printing parameters can be set to allow for the designed crystallinity within the 3D printed articles. For example, multiple parts with different energy densities can be printed to meet the desired mechanical requirements.

[0189] Table 17 Crystallinity of printed parts produced from polydioxanone + 3 wt% 10-micron UHA at different energy densities

[0190] <![CDATA[0.15J / mm 2 Unannealed 41.71 38.89 <![CDATA[0.2J / mm 2 Unannealed 43.18 39.55 <![CDATA[0.25J / mm 2 Unannealed 44.05 39.01 <![CDATA[0.3J / mm 2 Unannealed 47.31 43.66 <![CDATA[0.25J / mm 2 Annealing 48.14 39.55

[0191] Example 10

[0192] Using a base carrier to process other bioabsorbable polymers

[0193] In addition to the polydioxanone material printed on a 300×75×0.3mm base, additional materials also require a base carrier for successful part printing. Materials that benefit from a base carrier are polycaprolactone, polylactic acid (poly-L-lactide), and poly(lactic acid-co-glycolic acid). Without a base carrier, polycaprolactone and polylactic acid will curl and shrink. Any observed curling and shrinkage is significant for the position where the blade will engage and displace the printed article during recoating of a new powder layer. Poly(lactic acid-co-glycolic acid) benefits from the base because it is very brittle and will break during recoating when thin. Without a base anchoring layer, the part cannot be successfully printed.

[0194] Example 11

[0195] Mechanical results after processing

[0196] Depending on the processing method, the composition can possess controlled mechanical properties. For example, when processing polydioxanone + 3 wt% 10-micron unsintered calcium phosphate composite powder in a selective laser sintering machine, the mechanical properties of the printed article are highly dependent on the laser energy density and the part removal method. The effect of the printing method on mechanical properties was evaluated using a small stretch bar geometry. The energy density of the printing parameters used for two groups of mechanical samples was 0.25 J / mm². 3 .

[0197] If the printed article containing polydioxanone and 3% calcium phosphate is removed immediately after printing, the yield tensile strength is 20.65 ± 0.85 MPa, the modulus is 551 ± 11.5, and the elongation at break is 79.39 ± 40.64%. However, if the printed article is allowed to cool slowly within the system, the yield strength is 32 ± 0.47 MPa, the modulus is 827 ± 25.8 MPa, and the elongation at break is 9.36 ± 0.90%. Furthermore, the mechanically tested sample cooled during the process has a crystallinity of 48.14%, while the sample removed immediately after processing has a crystallinity of 44.05%. Mechanically tested samples were printed on a substrate structure within the print bed at 98 °C ± 1.5 °C. The Formiga P100 SLS machine used for this method required 4 hours to cool to room temperature of 25 °C. The data obtained indicate that if the cooling rate is controlled in the method, the articles printed from polydioxanone + 3% unsintered calcium sulfate can have the designed engineering stress.

[0198] Furthermore, the parts exhibit increased mechanical strength with increasing energy density settings. Parts produced at higher energy densities have higher tensile strength at break and more consistent elongation at break compared to parts produced at lower energy densities (Table 18). Multiple energy densities can be used within the print if desired. By doing so, portions of the printed 3D article can have internal structures specifically printed at higher energy densities to accommodate the mechanical loading direction. As an example, this can lead to highly personalized, optimized medical implant designs. Personalized medical implants can be printed using multiple energy densities in the mechanical loading direction of the final 3D article, allowing for optimization of tensile strength and modulus.

[0199] Table 18 Mechanical properties of polydioxanone + 3 wt% 10-micron UHA at different printing energy densities

[0200]

[0201]

[0202] Example 12

[0203] The effect of water-soluble salts on the mechanical properties of materials

[0204] The effect of water-soluble salts on the final mechanical properties of articles produced from polymer powder composites was evaluated by injection molding different compositions and testing the resulting tensile bars. Table 19-22 shows the mechanical results for different weight percentages of water-soluble salts in polydioxanone. All composite powder blends showed an increase in modulus with increasing weight percentage of water-soluble salts. Magnesium sulfate increased the elongation at break of the polymer composite with increasing weight percentage of water-soluble salts. Additionally, potassium chloride and sodium chloride salts had a significant effect on the elongation at break of the powder composites. None of the water-soluble salts significantly decreased or increased the yield tensile strength of the powder composites. This indicates that each water-soluble salt has a specific effect on the mechanical properties of the material. Combinations of multiple salts at different concentrations will be possible to design specific mechanical properties.

[0205] Table 19 Mechanical properties of polydioxanone with different weight percentages of magnesium sulfate

[0206]

[0207] Table 20 Mechanical properties of polydioxanone with different weight percentages of potassium chloride

[0208]

[0209] Table 21 Mechanical properties of polydioxanone with different weight percentages of sodium sulfate

[0210]

[0211] Table 22 Mechanical properties of polydioxanone with different weight percentages of sodium chloride

[0212]

[0213] Clause 1 Composite powder material, preferably having flow properties optimized for powder processing technology, comprises polymer powder and water-soluble salt.

[0214] The materials of Clause 2 and Clause 1, wherein water-soluble salts are embedded in the particle surface of polymer powder.

[0215] The materials of Clause 3 and Clause 1, wherein water-soluble salts are embedded in the particle surface of polymer powder by mixing or grinding.

[0216] Article 4. Materials of any one of Articles 1 to 3, wherein the polymer powder comprises processed polymer powder or unprocessed polymer powder.

[0217] The material of any one of Clauses 1 to 4 of Clause 5, wherein the polymer powder is a blend of virgin polymer powder and processed polymer powder; and wherein the processed polymer powder is annealed during laser sintering.

[0218] Article 6. The material of any one of Articles 1 to 5, wherein the polymer forming the polymer powder is prepared from p-dioxanone monomer, l-lactide monomer, d-lactide monomer, glycolide monomer, caprolactone monomer or a combination thereof.

[0219] Article 7. The material of any one of Articles 1 to 6, wherein the water-soluble salt is magnesium sulfate, sodium sulfate, potassium chloride, sodium chloride, sodium sulfate, potassium aluminum sulfate, magnesium chloride, or magnesium chloride hexahydrate or a mixture thereof.

[0220] The material of any one of Clauses 1 to 7 of Clause 8, wherein the water-soluble salt accounts for no more than about 50% by weight of the composite powder material, preferably between 0.01% by weight and 30% by weight, more preferably between 0.01% by weight and 20% by weight.

[0221] Article 9 The material of any one of Articles 1 to 8, wherein the polymer powder accounts for no more than about 99% by weight of the composite powder material, preferably between 70% and 95% by weight or between 80% and 99% by weight.

[0222] Clause 10: Method for manufacturing 3D articles, said 3D articles comprising a composite powder material of any one of Clauses 1 to 9, wherein the method comprises:

[0223] (a) A polymer base anchoring layer with a similar basic geometry is applied and irradiated to the 3D article being manufactured;

[0224] (b) Apply a layer of composite powder material to the printing area;

[0225] (c) Cross-sectional area of ​​a 3D article manufactured by sintering;

[0226] (d) Apply a multilayer composite powder material to the printing area on top of the base anchoring layer until the 3D product has been printed completely;

[0227] (e) Annealing the composite powder material for 1 second to 8 hours at a temperature preferably 8°C-60°C, more preferably 9°C-50°C, and most preferably 10°C-35°C below the initial polymer melt temperature; and

[0228] (f) Cool the composite powder material at a controlled cooling rate preferably from 0.1°C / min to 35°C / min, more preferably from 1°C / min to 20°C / min, and most preferably from 2°C / min to 5°C / min.

[0229] The method of Clause 11 and Clause 10, wherein the base anchoring layer of the irradiation is further supported by the base carrier below; or the base carrier is added to any structure other than the base geometry.

[0230] The method of Clause 12 and Clause 11, wherein the base carrier is irradiated with an energy density different from that used in manufacturing 3D articles by laser sintering.

[0231] The method of Clause 13, Clause 11, or Clause 12, wherein the base carrier can be removed from the manufactured 3D article; and wherein the base geometry can be separated into its initial powder form by sieving.

[0232] Article 14 The method of any one of Articles 10 to 13, wherein it can be achieved at 0.01 J / mm 3 Up to 5.0 J / mm 3 By altering the energy density of the laser sintering method, engineering stress is embedded into the manufactured 3D products.

Claims

1. A composite powder material comprising a polymer powder and a water-soluble salt, wherein the polymer powder comprises polydioxanone, and the water-soluble salt is a flow aid; and the water-soluble salt comprises 1% to 10% by weight of the composite powder material, wherein the water-soluble salt is embedded in the particle surface of the polymer powder. Water-soluble salts are embedded in the surface of polymer powder particles through grinding, and the composite powder material has flow properties optimized for powder processing technology.

2. The material according to claim 1, wherein the polymer forming the polymer powder is prepared from p-dioxanone monomer.

3. The material according to claim 1, wherein the water-soluble salt is magnesium sulfate, sodium sulfate, potassium chloride, sodium chloride, potassium aluminum sulfate, magnesium chloride, magnesium chloride hexahydrate, or a mixture thereof.

4. The material according to claim 1, wherein the polymer powder accounts for no more than 99% by weight of the composite powder material.

5. The material according to claim 1, wherein the polymer powder accounts for 70% to 95% by weight of the composite powder material.

6. The material according to claim 1, wherein the polymer powder accounts for 80% to 99% by weight of the composite powder material.

7. A method for manufacturing a 3D article comprising the composite powder material according to any one of claims 1 to 6, wherein the method comprises the following steps: (a) Applying and irradiating a polymer base anchoring layer with a similar base geometry to the 3D article being manufactured; (b) Apply the composite powder material layer to the printing area; (c) Cross-sectional area of ​​a 3D article being manufactured by sintering; (d) Apply multiple layers of composite powder material to the printing area on top of a polymer base anchoring layer with a similar basic geometry until the 3D article has been printed. (e) Anneal the composite powder material for 1 second to 8 hours at a temperature below the initial polymer melt temperature; and (f) Cooling the composite powder material at a controlled cooling rate.

8. The method of claim 7, wherein the method comprises the following steps: (e) Anneal the composite powder material for 1 second to 8 hours at a temperature 8°C to 60°C below the initial polymer melting temperature.

9. The method of claim 7, wherein the method comprises the following steps: (e) Anneal the composite powder material for 1 second to 8 hours at a temperature 9°C to 50°C below the initial polymer melt temperature.

10. The method of claim 7, wherein the method comprises the following steps: (e) Anneal the composite powder material for 1 second to 8 hours at a temperature 10°C to 35°C below the initial polymer melting temperature.

11. The method of claim 7, wherein the method comprises the following steps: (f) Cool the composite powder material at a controlled cooling rate of 0.1 °C / min to 35 °C / min.

12. The method of claim 7, wherein the method comprises the following steps: (f) Cool the composite powder material at a controlled cooling rate of 1°C / min to 20°C / min.

13. The method of claim 7, wherein the method comprises the following steps: (f) Cool the composite powder material at a controlled cooling rate of 2°C / min to 5°C / min.

14. The method according to any one of claims 7 to 13, wherein the polymer base anchoring layer having a similar base geometry is further supported by the underlying base carrier; or wherein the base carrier is added to any structure other than the base geometry.

15. The method of claim 14, wherein the base carrier is irradiated with an energy density different from that of the 3D article being manufactured by laser sintering.

16. The method of claim 14, wherein the base carrier is removed from the 3D article being manufactured; and wherein the base geometry is separated into its initial powder form by sieving.

17. The method according to any one of claims 7 to 13, wherein the concentration is 0.01 J / mm 3 Up to 5.0 J / mm 3 By altering the energy density of laser sintering methods, engineering stresses can be embedded into the 3D products being manufactured.

Citation Information

Patent Citations

  • Biocompatible polymer powders for additive manufacturing

    WO2019043137A1

  • Three-dimensional structure and its manufacturing method

    JP2007301945A

  • Method of Fabricating Porous Scaffold for TissueEngineering

    KR100537404B1

  • The method for fabrication of scaffold using salt-leaching technique

    KR1020120045480A

  • Selective laser sintering of polymer powder of controlled particle size distribution

    US5817206A